A fiber-free low-carbon SMA asphalt mixture and mixing method thereof

By removing wood fibers and using surfactant compounding and optimizing grading, the high cost and poor environmental protection and energy saving of traditional SMA asphalt mixtures are solved, and the preparation of low-carbon SMA asphalt mixtures is realized, reducing construction temperature and Energy consumption improves road surface performance and environmental protection.

CN118479795BActive Publication Date: 2024-12-20LUAN GONGXIN ROAD MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410590924.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-13
Publication Date
2024-12-20
Estimated Expiration
2044-05-13

AI Technical Summary

Technical Problem

Traditional SMA asphalt mixtures have high costs, complex production procedures, uneven dispersion of wood fibers, and poor environmental protection and energy saving in the production process, especially energy consumption and waste emissions caused by high temperature heating.

Method used

By removing wood fibers, using surfactant compounding and optimizing SMA grading, reducing mixing temperature, reducing energy consumption and exhaust gas emissions, and improving the structural stability of the mixture by optimizing the mass ratio and particle size distribution of asphalt to ore, improving the structural stability of the mixture by optimizing the mass ratio and particle size distribution of asphalt to ore and viscosity to avoid leakage and oil spread.

Benefits of technology

It has achieved the reduction of construction temperature, production costs, and improvement of road compaction and durability, significantly improving the mechanical and environmental protection performance of the mixture, and reducing greenhouse gas emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118479795B_ABST
    Figure CN118479795B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a fiber-free low-carbon SMA asphalt mixture. The fiber-free low-carbon SMA asphalt mixture comprises raw materials of mineral material and asphalt, wherein the mass ratio of asphalt to mineral material is (4.8-5.8):100; the mineral material comprises 10-17 mm coarse aggregate, 5-10 mm coarse aggregate, machine-made sand and mineral powder, wherein the mass ratio of 10-17 mm coarse aggregate, 5-10 mm coarse aggregate, machine-made sand and mineral powder is (31-32):(43-44):(14-15):(10-11); the asphalt contains a surfactant with a mass content of 0.5%; the surfactant is a mixture of fatty amine polyoxyethylene ether, fatty alcohol polyoxyethylene ether, epoxy soybean oil and cocamidopropyl hydroxysulfobetaine. The present application reduces the mixing temperature, reduces energy consumption and exhaust emissions, increases asphalt viscosity, removes wood fibers in the SMA mixture, and prevents leakage and oil overflow in the SMA mixture through the selection and compounding of surfactants and the optimization of SMA grading; at the same time, it reduces the amount of asphalt used and improves structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a fiber-free low-carbon SMA asphalt mixture, which is a preparation technology of an environmentally friendly and energy-saving pavement material and belongs to the technical field of road engineering. Background Art

[0002] SMA (mashy asphalt crushed stone mixture) is currently internationally recognized (and widely used) as an asphalt surface mixture with strong deformation resistance and good durability. Due to the good embedding of coarse aggregate, the mixture has very good high-temperature rutting resistance. At the same time, due to the bonding effect of mastic asphalt, the low-temperature deformation performance and water stability are also greatly improved. Adding fiber stabilizers can keep the asphalt binder at a high viscosity, and its paving and compaction effects are better. Intermittent grading forms large pores on the surface, with a large structural depth and good anti-skid performance. At the same time, the void ratio of the mixture is very small, and the aging resistance and durability are very good, which comprehensively improves the road performance of asphalt mixtures and becomes one of the most common structural forms of highway pavements.

[0003] However, in the actual production of SMA asphalt mixture, the addition of wood fiber not only increases the mixing time and difficulty, but also often causes agglomeration due to the difficulty in dispersing wood fiber, forming oil spots on the road surface, affecting the road quality. In other words, SMA asphalt mixture itself still has many disadvantages:

[0004] 1) High cost: Traditional SMA asphalt mixture is expensive and is generally only used on highways.

[0005] 2) Complex production process: SMA asphalt mixture production requires the addition of wood fiber agents, which increases the process and mixing time;

[0006] 3) Uneven dispersion of wood fiber: wood fiber is difficult to disperse in the mixing pot, which easily causes agglomeration and sludge;

[0007] 4) Poor environmental protection and energy saving: The heating temperature of traditional SMA reaches 175-185℃, which increases energy consumption and emissions. Summary of the invention

[0008] The present invention provides a method for preparing a fiber-free low-carbon SMA asphalt mixture, which removes wood fiber in a traditional SMA asphalt mixture, reduces cost and construction complexity, lowers construction temperature, reduces energy consumption and waste emissions, and is an environmentally friendly and energy-saving pavement material.

[0009] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:

[0010] A fiber-free low-carbon SMA asphalt mixture, whose raw materials include: mineral material and asphalt, wherein the mass ratio of asphalt to mineral material (i.e., oil-stone ratio) is (4.8-5.8):100; the mineral material includes: 10-17 mm coarse aggregate, 5-10 mm coarse aggregate, machine-made sand and mineral powder, and the mass ratio of 10-17 mm coarse aggregate, 5-10 mm coarse aggregate, machine-made sand and mineral powder is (31-32):(43-44):(14-15):(10-11); the asphalt contains a surfactant with a mass content of 0.5%; the surfactant is a mixture of fatty amine polyoxyethylene ether, fatty alcohol polyoxyethylene ether, epoxy soybean oil and cocamidopropyl hydroxysulfonyl betaine.

[0011] The wood fiber in SMA mixture mainly plays the role of absorbing asphalt, stabilizing the structure, increasing the bonding force, and reducing the segregation and oiling of the mixture during mixing, transportation, and paving. Therefore, the key to removing the fiber in SMA mixture is to solve the two problems of asphalt leakage in the mixture and the stability of the mixture skeleton.

[0012] The present application reduces the mixing temperature, reduces energy consumption and exhaust emissions, increases asphalt viscosity, removes wood fibers in the SMA mixture, and prevents leakage and oil overflow in the SMA mixture through the selection and compounding of surfactants and the optimization of SMA grading; at the same time, it reduces the amount of asphalt used and improves structural stability.

[0013] The above surfactant is an oily mixture.

[0014] The surfactant comprises 5-15 parts of dodecylamine polyoxyethylene ether, 40-50 parts of octadecylamine fatty amine polyoxyethylene ether, 2-15 parts of epoxidized soybean oil and 20-30 parts of fatty alcohol polyoxyethylene ether, and the parts are by mass.

[0015] As one preferred implementation scheme, the above surfactant also includes 0.5 to 1.5 parts of cocamidopropyl hydroxysulfonyl betaine, where the parts are by mass. Cocamidopropyl hydroxysulfonyl betaine has a significant promoting effect.

[0016] In order to further improve the mechanical properties of fiber-free low-carbon SMA asphalt mixture, the mass ratio of asphalt to mineral aggregate is (4.8-5.4): 100. More preferably, the mass ratio of asphalt to mineral aggregate is 5.3: 100; the mass ratio of 10-17 mm coarse aggregate, 5-10 mm coarse aggregate, machine-made sand and mineral powder is 32: 43: 14: 11.

[0017] The above-mentioned asphalt is SBS modified asphalt with a softening point of ≥75°C, an elongation of ≥30cm at 15°C, and a needle penetration (0.1mm) of 40 to 70 at 25°C.

[0018] The above-mentioned coarse aggregate with a particle size of 5 to 10 mm and the coarse aggregate with a particle size of 10 to 17 are basalt; the fine aggregate is limestone machine-made sand.

[0019] In order to achieve better structural stability, on the basis of meeting the Technical Specifications for Highway Asphalt Pavement Construction, the gradation of mineral materials was optimized as follows. The gradation of mineral materials was calculated by the mass percentage passing through the square hole sieve, which were: 100% of the mineral materials passing through the 16mm square hole sieve, 93.4-93.6% of the mineral materials passing through the 13.2mm square hole sieve, 67.7-68.6% of the mineral materials passing through the 9.5mm square hole sieve, and 28.7-28.6% of the mineral materials passing through the 4.75mm square hole sieve. 28.8%, 22.9-23% of the ore passed through the 2.36mm square hole sieve, 18.5-18.9% of the ore passed through the 1.18mm square hole sieve, 16.4-17.0% of the ore passed through the 0.6mm square hole sieve, 13.4-14.2% of the ore passed through the 0.3mm square hole sieve, 12.0-12.8% of the ore passed through the 0.15mm square hole sieve, and 10.2-11.0% of the ore passed through the 0.075mm square hole sieve. The present application improves the passing rate of the 0.075mm sieve hole, increases the amount of 5-10mm aggregate, and enhances the structural stability.

[0020] Further preferably, the grading of the mineral material is calculated by the mass percentage passing through the square hole sieve, which is: 100% of the mineral material passes through the 16 mm square hole sieve, 93.4% of the mineral material passes through the 13.2 mm square hole sieve, 67.7% of the mineral material passes through the 9.5 mm square hole sieve, 28.7% of the mineral material passes through the 4.75 mm square hole sieve, 23% of the mineral material passes through the 2.36 mm square hole sieve, 18.9% of the mineral material passes through the 1.18 mm square hole sieve, 17.0% of the mineral material passes through the 0.6 mm square hole sieve, 14.2% of the mineral material passes through the 0.3 mm square hole sieve, 12.8% of the mineral material passes through the 0.15 mm square hole sieve, and 11.0% of the mineral material passes through the 0.075 mm square hole sieve.

[0021] The mixing method of the fiber-free low-carbon SMA asphalt mixture comprises the following steps:

[0022] 1) Heat the SBS modified asphalt to 130-140°C, add surfactant and mix well;

[0023] 2) Use thermal radiation heating to heat the new aggregate, asphalt and mineral powder to 130-140°C;

[0024] 3) Dry mix 10-17 mm coarse aggregate, 5-10 mm coarse aggregate and machine-made sand at a temperature of 130-140° C. for 60 seconds, add the asphalt prepared in step 1) at a temperature of 130-140° C., mix for 60 seconds, and finally add mineral powder at a temperature of 130-140° C. and mix for 60 seconds.

[0025] The technologies not mentioned in the present invention are all referred to the prior art.

[0026] The method for preparing the fiber-free low-carbon SMA asphalt mixture of the present invention has the following beneficial effects:

[0027] 1. Reduce construction temperature and improve construction and workability: Without adding fiber stabilizers and reducing the amount of asphalt, ensure that the SMA asphalt mixture is mixed at a lower temperature, without segregation and oiling, and improve the compaction of the road surface. The lower production temperature will directly reduce the short-term aging damage of asphalt and mixture, and produce less greenhouse gas and harmful smoke emissions, so as to obtain a lower carbon, durable and economical asphalt pavement.

[0028] 2. Reduce production costs: Eliminating wood fiber reduces direct costs, reduces one process, avoids problems such as agglomeration and sludge caused by uneven dispersion of wood fiber, improves production efficiency, and increases output.

[0029] 3. The road performance is better than that of traditional SMA asphalt mixture: The use of fibers in traditional SMA is mainly to retain the asphalt in the mixture, rather than to fill the voids in the mixture. The core of the low-carbon SMA of this application is to reduce the production temperature through warm mix technology to increase the viscosity of the mortar, which helps the asphalt to better adhere to the aggregate to resist leakage, thereby removing additional fibers and asphalt. The relatively low asphalt content of this application can be sufficient to fill the internal asphalt structure when the overall fiber-free mixture aggregate is fully embedded, so that the low-carbon SMA can achieve the same film thickness as conventional SMA mixtures, and various indicators are better than conventional SMA, especially strength, water resistance, anti-dispersion, high temperature stability (dynamic stability), etc., which are significantly improved.

[0030] 4. The present application is a SMA made of hot-mixed and hot-laid heat-modified asphalt. Compared with the SMA made of cold-mixed and cold-laid emulsified asphalt, the durability of the present application is significantly superior. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The present invention is a flow chart of the preparation method of the fiber-free low-carbon SMA asphalt mixture;

[0032] Figure 2 The finished product picture (right) and construction drawing (left) of the fiber-free SMA asphalt mixture of the present invention;

[0033] Figure 3 This is a test diagram of the fiber-free SMA asphalt mixture of the present invention;

[0034] Figure 4 It is the mixture gradation curve diagram in Example 1;

[0035] Figure 5is the performance diagram of the mixture in Example 1;

[0036] Figure 6 This is a photo of the mixture in Example 1 after compaction of the rutting specimen;

[0037] Figure 7 This is a photo of the mixture in Example 2 after compaction of the rutting specimen; DETAILED DESCRIPTION

[0038] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0039] The raw materials for each case are as follows:

[0040] 1. Asphalt uses SBS modified asphalt from Nanjing Refinery:

[0041]

[0042] 2. Aggregate:

[0043] The coarse aggregate is basalt, which comes from Poyang County, Jiangxi Province, and has two sizes: 5-10mm and 10-17mm. The fine aggregate is limestone machine-made sand, with a particle size of less than 5mm, and the mineral powder is ground from limestone.

[0044]

[0045]

[0046] 3. Mineral powder:

[0047]

[0048] Mineral powder, made from limestone, was provided by Lu'an Gongxin Road Materials Co., Ltd.

[0049] Dodecylamine polyoxyethylene ether (AC-1202), Shanghai Huijun Chemical Co., Ltd.; octadecylamine fatty amine polyoxyethylene ether (AC-1812), Nantong Jienuo Chemical Co., Ltd.; fatty alcohol polyoxyethylene ether (isomeric alcohol ether E-1308), Zhonghe Shengtai; cocamidopropyl hydroxysulfobetaine (RY 35CH), Guangzhou Huazhiwang Chemical Co., Ltd.; epoxidized soybean oil, industrial grade, Shandong Zhouhe Chemical Co., Ltd.

[0050] Example 1

[0051] The raw materials of a fiber-free low-carbon SMA asphalt mixture include: 10-17 mm coarse aggregate, 5-10 mm coarse aggregate, machine-made sand, mineral powder and asphalt, wherein the mass ratio of asphalt to the mass sum of 10-17 mm coarse aggregate, 5-10 mm coarse aggregate, machine-made sand and mineral powder (i.e., oil-stone ratio) is 5.2:100; the asphalt contains surfactants with mass contents of 0.3%, 0.4% and 0.5%; the surfactant is a mixture of dodecylamine polyoxyethylene ether, octadecylamine fatty amine polyoxyethylene ether, epoxy soybean oil, fatty alcohol polyoxyethylene ether and cocoamidopropyl hydroxysulfobetaine with a mass ratio of 15:50:5:30:1; the mass ratio of 10-17 mm coarse aggregate, 5-10 mm coarse aggregate, machine-made sand and mineral powder is 31:44:15:10.

[0052] Mineral screening and synthetic grading

[0053]

[0054]

[0055] The mixing method of the above fiber-free low-carbon SMA asphalt mixture is:

[0056] 1) Heat the SBS modified asphalt to 130-140°C, add surfactant and mix well;

[0057] 2) Use thermal radiation heating to heat the new aggregate, asphalt and mineral powder to 130-140°C;

[0058] 3) Dry mix 10-17 mm coarse aggregate, 5-10 mm coarse aggregate and machine-made sand at a temperature of 130-140° C. for 60 seconds, add the asphalt prepared in step 1) at a temperature of 130-140° C., mix for 60 seconds, and finally add mineral powder at a temperature of 130-140° C., mix for 60 seconds, and discharge.

[0059] The fiber-free low-carbon SMA asphalt mixture is constructed according to the following steps: discharging at 130-140°C, paving at 115-125°C, and rolling with a roller, wherein the initial rolling temperature is 110-120°C and the final rolling temperature is greater than or equal to 90°C; the open traffic temperature is less than or equal to 50°C.

[0060] Performance test of the above fiber-free low-carbon SMA asphalt mixture:

[0061] Resistance to water damage: The water stability of SMA-13 ​​mixture was evaluated by residual stability and splitting tests. The specific results are as follows:

[0062] Results of residual stability test of SMA-13 ​​mixture

[0063]

[0064] Results of SMA-13 ​​mixture splitting test

[0065]

[0066] High temperature stability: Dynamic stability is used to evaluate the high temperature stability of SMA-13 ​​mixture. The test method is rutting test, and the specific results are as follows:

[0067] SMA-13 ​​mixture rutting test results

[0068]

[0069] Other test indicators:

[0070]

[0071]

[0072] Figure 6 This is a photo of the mixture in this example after compaction of the rutting specimen. It can be seen that oil spots appear on about 1 / 4 of the area.

[0073] Example 2

[0074] The raw materials of a fiber-free low-carbon SMA asphalt mixture include: 10-17 mm coarse aggregate, 5-10 mm coarse aggregate, machine-made sand, mineral powder and asphalt, wherein the mass ratio of asphalt to the mass sum of 10-17 mm coarse aggregate, 5-10 mm coarse aggregate, machine-made sand and mineral powder (i.e., oil-stone ratio) is 5.3:100; the asphalt contains a surfactant with a mass content of 0.5%; the surfactant is a mixture of dodecylamine polyoxyethylene ether, octadecylamine fatty amine polyoxyethylene ether, epoxy soybean oil, fatty alcohol polyoxyethylene ether and cocoamidopropyl hydroxysulfobetaine with a mass ratio of 15:50:5:30:1; the mass ratio of 10-17 mm coarse aggregate, 5-10 mm coarse aggregate, machine-made sand and mineral powder is 32:43:14:11.

[0075] Mineral screening and synthetic grading

[0076]

[0077]

[0078] The mixing method of the above fiber-free low-carbon SMA asphalt mixture is:

[0079] 1) Heat the SBS modified asphalt to 130-140°C, add surfactant and mix well;

[0080] 2) Use thermal radiation heating to heat the new aggregate, asphalt and mineral powder to 130-140°C;

[0081] 3) Dry mix 10-17 mm coarse aggregate, 5-10 mm coarse aggregate and machine-made sand at a temperature of 130-140° C. for 60 seconds, add the asphalt prepared in step 1) at a temperature of 130-140° C., mix for 60 seconds, and finally add mineral powder at a temperature of 130-140° C., mix for 60 seconds, and discharge.

[0082] The fiber-free low-carbon SMA asphalt mixture is constructed according to the following steps: discharging at 130-140°C, paving at 115-125°C, and rolling with a roller, wherein the initial rolling temperature is 110-120°C and the final rolling temperature is greater than or equal to 90°C; the open traffic temperature is less than or equal to 50°C.

[0083] Figure 7 This is a photo of the mixture in Example 5 after compaction of the rutting specimen. It can be seen that there is no oil spillage.

[0084] Comparative Example 1

[0085] The raw materials of traditional SMA-13 ​​asphalt mixture include: 10-17mm coarse aggregate, 5-10mm coarse aggregate, machine-made sand, mineral powder, asphalt and wood fiber, among which the ratio of the mass of asphalt to the sum of the mass of 10-17mm coarse aggregate, 5-10mm coarse aggregate, machine-made sand and mineral powder (also known as the oil-stone ratio) is 6.3:100; the mass amount of wood fiber relative to asphalt is 0.3%; the mass ratio of 10-17mm coarse aggregate, 5-10mm coarse aggregate, machine-made sand and mineral powder is 35:40:15:10.

[0086] The grading is as follows:

[0087]

[0088] Mixing test:

[0089] Traditional SMA-13 ​​asphalt mixture: After the aggregate (10-17mm coarse aggregate, 5-10mm coarse aggregate and machine-made sand) is heated to 200℃, wood fiber is added and mixed for 60S, then SBS modified asphalt is added and mixed for 60S, and finally mineral powder is added and mixed for 60S before discharging.

[0090] The above mix proportions can all meet the mix proportion design requirements in the "Technical Specifications for Highway Asphalt Pavement Construction" (JTGF40-2004).

[0091] Two batches of mixture were prepared in each case, and the first batch of mixture was used for extraction test to ensure the stability of mixture gradation. After the gradation was confirmed to be stable, Marshall specimens and rutting plate specimens were made at the same discharging, compaction and molding temperatures.

[0092]

[0093] As can be seen from the table, the fiber-free SMA-13 ​​mixture of the present invention has better performance than the traditional SMA-13 ​​mixture and far meets the specification requirements. If the dodecylamine polyoxyethylene ether, octadecylamine fatty amine polyoxyethylene ether, epoxy soybean oil or fatty alcohol polyoxyethylene ether in Example 2 are omitted, the mixing temperature will be significantly increased, and cocamidopropyl hydroxysulfobetaine has a significant promoting effect on the remaining components.

Claims

1. A fiber-free low-carbon SMA asphalt mixture, characterized by: Its raw materials include: mineral material and asphalt, wherein the mass ratio of asphalt to mineral material is (4.8-5.3):100; the mineral material includes: 10-17 mm coarse aggregate, 5-10 mm coarse aggregate, machine-made sand and mineral powder, and the mass ratio of 10-17 mm coarse aggregate, 5-10 mm coarse aggregate, machine-made sand and mineral powder is (31-32):(43-44):(14-15):(10-11); the asphalt contains a surfactant with a mass content of 0.5%; the surfactant includes 5-15 parts of dodecylamine polyoxyethylene ether, 40-50 parts of octadecylamine fatty amine polyoxyethylene ether, 2-15 parts of epoxy soybean oil, 20-30 parts of fatty alcohol polyoxyethylene ether and 0.5-1.5 parts of cocamidopropyl hydroxysulfonyl betaine, and the parts are by mass; The asphalt is SBS modified asphalt; The mixing method of the fiber-free low-carbon SMA asphalt mixture comprises the following steps: 1) Heat the SBS modified asphalt to 130~140℃, add surfactant and mix well; 2) Heat the mineral materials to 130~140℃ by thermal radiation heating; 3) Dry mix 10-17 mm coarse aggregate, 5-10 mm coarse aggregate and machine-made sand at a temperature of 130-140°C for 50-60 seconds, add the asphalt prepared in step 1) at a temperature of 130-140°C, mix for 50-60 seconds, and finally add mineral powder at a temperature of 130-140°C and mix for 50-60 seconds.

2. The fiber-free low-carbon SMA asphalt mixture according to claim 1, characterized in that: The softening point of asphalt is ≥75℃, the elongation at 15℃ is ≥30cm, and the needle penetration of 0.1mm at 25℃ is 40~70.

3. The fiber-free low-carbon SMA asphalt mixture according to claim 1 or 2, characterized in that: The coarse aggregate with a particle size of 5-10 mm and the coarse aggregate with a particle size of 10-17 mm are basalt; the machine-made sand is limestone machine-made sand.

4. The fiber-free low-carbon SMA asphalt mixture according to claim 1 or 2, characterized in that: The grading of mineral materials is calculated by the mass percentage passing through the square hole sieve, which is: 100% of the mineral materials passing through the 16mm square hole sieve, 93.4~93.6% of the mineral materials passing through the 13.2mm square hole sieve, 67.7~68.6% of the mineral materials passing through the 9.5mm square hole sieve, 28.7~28.8% of the mineral materials passing through the 4.75mm square hole sieve, 22.9~23% of the mineral materials passing through the 2.36mm square hole sieve, 18.5~18.9% of the mineral materials passing through the 1.18mm square hole sieve, 16.4~17.0% of the mineral materials passing through the 0.6mm square hole sieve, 13.4~14.2% of the mineral materials passing through the 0.3mm square hole sieve, 12.0~12.8% of the mineral materials passing through the 0.15mm square hole sieve, and 10.2~11.0% of the mineral materials passing through the 0.075mm square hole sieve.

5. The fiber-free low-carbon SMA asphalt mixture according to claim 4, characterized in that: The grading of mineral materials is calculated by the mass percentage passing through the square hole sieve, which are: 100% of the mineral materials pass through the 16mm square hole sieve, 93.4% of the mineral materials pass through the 13.2mm square hole sieve, 67.7% of the mineral materials pass through the 9.5mm square hole sieve, 28.7% of the mineral materials pass through the 4.75mm square hole sieve, 23% of the mineral materials pass through the 2.36mm square hole sieve, 18.9% of the mineral materials pass through the 1.18mm square hole sieve, 17.0% of the mineral materials pass through the 0.6mm square hole sieve, 14.2% of the mineral materials pass through the 0.3mm square hole sieve, 12.8% of the mineral materials pass through the 0.15mm square hole sieve, and 11.0% of the mineral materials pass through the 0.075mm square hole sieve.

6. The fiber-free low-carbon SMA asphalt mixture according to claim 1 or 2, characterized in that: The mass ratio of asphalt to mineral aggregate is 5.3:100; the mass ratio of 10~17mm coarse aggregate, 5~10mm coarse aggregate, machine-made sand and mineral powder is 32:43:14:11.

Citation Information

Patent Citations

  • Zwitter-ion and nonionic composite asphalt warm-mixing agent and preparation method thereof

    CN104559251A

  • SMA mixture and its preparation method and construction method

    CN106082788A

  • Plasticized modified warm-mixing agent and warm-mixed asphalt preparation method

    CN113248809A